Mental Health Service Preferences of University Students in Sleman Regency - Arifudin, Moch.; Purwanti, Sri (BKM Public Health and Community Medicine, 2024)
Purpose: The role of mental health services in higher education is crucial in responding to the increasing cases of suicide among students. Universities are expected to provide solutions in this regard. Although several facilities have been made available to ensure easy access, not all provided services align with students' needs and preferences. Therefore, assessing students' preferences for mental health services is necessary. Methods: This study focuses on examining the preferences of university students in Sleman Regency regarding mental health services. Using a qualitative method, data were collected through in-depth interviews with fifteen students from various universities in Sleman. The data analyzed included background, experiences, and preferences based on the services deemed suitable and essential by the students. Results: The findings reveal that students prefer online mental health services over face-to-face meetings. Reasons for this preference include the high intensity of student interactions online, comfort in expressing feelings online, and anxiety about direct interactions. The implication of this study is the importance of enhancing and refining mental health services at the university level to meet student needs more effectively. Conclusion: There is a need to provide mental health services on campus that align with student preferences and needs to ensure their effectiveness and relevance in addressing the rising trend of mental health issues among students.